Phytochemical Screening and In-Vitro Evaluation of Antioxidant Activities of Various Extracts of Leaves and Stems of Kalanchoe crenata - Manisha Bhatti; Anjoo Kamboj; Ajay Kumar Saluja (Journal of Pharmacy and Nutrition Sciences, 2012)
Many diseases are associated with oxidative stress caused by free radicals. Current research is directed towards finding naturally occurring antioxidants of plant origin. Kalanchoe crenata Andr. (Crassulaceae), commonly known as "never die" or "Dog’s liver," has been traditionally used for the treatment of ailments, such as, earache, smallpox, headache, inflammation, pain, asthma, palpitations, convulsion, and general debility. The aim of present research deals with phytochemical screening and in-vitro evaluation of antioxidant activities of the leaves & stems of K.crenata. Method: Successive extracts of leaves & stems was subjected for phytochemical screening. The preliminary screening reports the presence of saponins, phytosterols, flavanoids, phenols and alkaloids in the extracts. Various extracts of K.crenata leaves & stems was studied in-vitro for total antioxidant activity, for scavenging of nitric oxide, hydrogen peroxide, the antioxidant capacity by phosphomolybdenum, reducing power determination and determination of phenolic and flavonoid content in the extracts. 1,1-Diphenyl-2-picrylhydryzyl (DPPH) scavenging activity or the hydrogen donating capacity was quantified in presence of stable DPPH radical on the basis of Blois method. Nitric Oxide (NO) radical scavenging method was performed in the presence of nitric oxide generated from sodium nitroprusside using ascorbic acid as standard in both methods. The phenolic content was determined by using Folin-Ciocalteu reagent and flavonoid content was determined by aluminum chloride. Result: The radical scavenging activity was found to dose dependent. Thus extract has been established as an antioxidant. The reducing capacity serves as significant indicator of antioxidant activity. The reducing power was found to increase with the increasing concentration of extract. The 100mg plant powder yielded 0.34, 0.49, 0.72, 0.98%w/wand 0.15, 0.23, 0.39, 0.56%w/w phenolic content in the benzene, chloroform, acetone, ethanol extracts of leaves and stems respectively using gallic acid as standard. Plant contains about 0.19, 0.29, 0.48, 0.64%w/w and 0.11, 0.17, 0.32, 0.47 %w/w of flavonoid content in the benzene, chloroform, acetone, ethanol extracts of leaves and stems respectively using quercetin as standard. Conclusion: The present study provides evidence that different extracts of K.crenata leaves and stems is potential source of antioxidant activity. The extracts were found to contain phenolic compounds which could be responsible for the antioxidant properties. So K. crenata traditional use is justified in the present research work.